ANALYSIS OF REGIONAL INEQUALITY AND ECONOMIC POTENTIAL IN THE KEDUNGSEPUR AREA 2017-2021 - Ilham Al Majiid; Nenik Woyanti (JABE (Journal of Applied Business and Economic), 2023)
This study intends to classify economic growth patterns between districts/cities, analyze the level of regional inequality, and identify sectors with the potential to be evolved to strengthen the regional economy in the Kedungsepur area. Secondary data is used in this study, which was processed using Klassen Typology, Theil Index, Williamson Index, Shift-Share, and Location Quotient analysis. The findings indicate that the majority of the growth patterns of districts/cities in Kedungsepur are relatively underdeveloped regions. Inequality across districts/cities in the Kedungsepur region is relatively significant and is expected to rise in 2017-2021. Economic potentials that are useful for encouraging regional economic growth in the Kedungsepur area are the mining and services industries in Grobogan Regency; the services industry in Demak Regency; the educational services industry in Semarang Regency; the agriculture and mining industries in Kendal Regency; the accommodation and food service industry and the company services industry in Salatiga City; as well as the communication and information industry in Semarang City